2021
DOI: 10.1042/bsr20204114
|View full text |Cite|
|
Sign up to set email alerts
|

Preventive role of probiotic bacteria against gastrointestinal diseases in mice caused by Giardia lamblia

Abstract: Giardiasis is one of the most prevalent gastrointestinal diseases in the world. It is caused by Giardia, Giardia lamblia, a common and opportunistic zoonotic parasite. The aim of our work is to find a natural and safe alternative treatment for giardiasis, specifically, to determine if probiotic bacteria (Lactobacillus acidophilus, Bifidobacterium bifidum, and L. helveticus) can contribute to treatment, and act as preventives. Sixty weanling albino mice, Mus musculus, were divided into control and experimental,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Whereas the antibacterial and antifungal activity [31,32] of L. acidophilus has been well illustrated, the antiparasitic properties of L. acidophilus have been less studied. Studies with mouse models of the diseases caused by Giardia lamblia [33], Toxocara canis [34], Trichinella spiralis [35], and Cryptosporidium parvum [36] reveal that a combination of probiotics and other probiotic strains is beneficial in the treatment and prevention of these parasites. In a recent study, we demonstrated that L. acidophilus is detrimental to E. histolytica but the amebicide mechanism was unknown [19].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the antibacterial and antifungal activity [31,32] of L. acidophilus has been well illustrated, the antiparasitic properties of L. acidophilus have been less studied. Studies with mouse models of the diseases caused by Giardia lamblia [33], Toxocara canis [34], Trichinella spiralis [35], and Cryptosporidium parvum [36] reveal that a combination of probiotics and other probiotic strains is beneficial in the treatment and prevention of these parasites. In a recent study, we demonstrated that L. acidophilus is detrimental to E. histolytica but the amebicide mechanism was unknown [19].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the antibacterial and antifungal activity [33,34] of L. acidophilus has been well illustrated, the antiparasitic properties of L. acidophilus has been less studied. L. acidophilus in combination with other probiotics is beneficial in the prevention and treatment of Giardia lamblia infection in mice [35], Toxocara canis [36], Trichinella spiralis [37] and Cryptosporidium parvum [38]. In a recent work, we have demonstrated that L. acidophilus is detrimental to E. histolytica but the amebicide mechanism was unknown [19].…”
Section: Discussionmentioning
confidence: 99%
“…These finding strengthen our understanding about the role of resident normal microflora of the intestine that can stimulate the pathogenicity of some intestinal protozoan. Beside normal microflora, probiotics have the potency to prevent evolution of some protozoan parasite; which will be discuss in the following section [61].…”
Section: Hypotheses Regarding Protozoan Pathogenic Stimulation By The...mentioning
confidence: 99%
“…Probiotics inhibits the advancement of certain intestinal pathogens [61,62]. Probiotics also effective and efficient in the supportive management of gastrointestinal disorders [61,62], infection based respiratory disease [63], and allergic symptoms [64], and "also can kill or inhibit or even kills strain-specific pathogens" [65] through several mechanisms, namely (1) Competition [66], (2) Molecule secretion [67], and/or (3) Immune induction [62].…”
Section: The Potency Of Probiotics Against Protozoan Parasitesmentioning
confidence: 99%